2009
DOI: 10.1080/17450120903039977
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting causal pathways contribute to poorer health and nutrition outcomes in orphans in Zimbabwe

Abstract: Orphaned children have been found to be at greater risk of poor health and malnutrition compared to non-orphans in sub-Saharan African countries. However, levels of disadvantage vary by location and little is known about the causal pathways that lead from orphanhood to poorer health and malnutrition. Aggregate data from recent Demographic and Health Surveys in 22 countries were used to compare overall levels of ill-health and malnutrition by orphan status. Data from the Manicaland Child Cohort Study in Zimbabw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
(27 reference statements)
1
7
0
Order By: Relevance
“…It is interesting to note that the analysis presented here provides no evidence that paternal orphans or children in household where other adult household members (other than mother) are HIV positive, or living in communities or countries with higher HIV prevalence are more undernourished than those in less affected households or communities. These findings, though consistent with patterns observed in specific settings in sub-Saharan Africa ( Bridge et al., 2006; Owen et al., 2009; Zidron et al., 2009 ), call for further research to better understand the possible mechanisms. Possible explanations for lack of differences in nutritional status between orphans and non-orphans have included the possibility that orphans live in wealthier households than non-orphans ( Zidron, et al., 2009 ).…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…It is interesting to note that the analysis presented here provides no evidence that paternal orphans or children in household where other adult household members (other than mother) are HIV positive, or living in communities or countries with higher HIV prevalence are more undernourished than those in less affected households or communities. These findings, though consistent with patterns observed in specific settings in sub-Saharan Africa ( Bridge et al., 2006; Owen et al., 2009; Zidron et al., 2009 ), call for further research to better understand the possible mechanisms. Possible explanations for lack of differences in nutritional status between orphans and non-orphans have included the possibility that orphans live in wealthier households than non-orphans ( Zidron, et al., 2009 ).…”
Section: Discussionsupporting
confidence: 76%
“…The second limitations relates to the data on parents’’survivorship status. The analysis has only included paternal survivorship, even though previous studies have suggested that it is maternal or double orphans who are more likely to suffer ill-health and malnutrition ( Owen et al. 2009 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…10 Numerous studies from sub-Saharan Africa have found that these constraints on families and traditional caregiving may be associated with worse educational, health, and other outcomes among orphaned children, which have been widely documented in family-based settings. 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19…”
Section: Introductionmentioning
confidence: 99%